Double transition of young migrants in Luxembourg: vulnerable, resilient and empowering integration trajectories in the period of youth - Oliveira, José; Nienaber, Birte; Bissinger, Jutta; Gilodi, Amalia; Richard, Catherine; Albert, Isabelle (Frontiers in Sociology, 2024)
Migrant integration trajectories have become more complex, open, uncertain, and continuously changing, over time. For young migrants, their integration endeavour intersects with their process of transition to adulthood, a double transition that poses additional challenges. Recent theoretical perspectives such as “liquid integration” aim at focusing on the dynamic, processual, and temporal nature of migrant integration. The present article focuses on the dynamic interplay of obstacles and enablers that, over time, interact to construct complex, often non-linear, and open-ended integration and coming of age trajectories of young migrants (aged from 18 to 30 years) coming from outside the European Union (EU) to EU countries. Empirical results from the H2020 MIMY (Empowerment through liquid Integration of Migrant Youth in vulnerable conditions) research project in Luxembourg will be presented. In order to address the goal of the research, qualitative data were gathered by means of N = 38 interviews with young migrants with different migratory paths, characteristics and experiences, and specifically included: young migrants from non-EU Portuguese-speaking countries (N = 16), refugees living in reception centres (N = 15), migrants who since arriving in Luxembourg have become publicly visible (N = 7). Content analysis of the interviews allowed a twofold purpose: (1) capturing the unfolding of intersectional integration obstacles that over time play a decisive role in the building of conditions of vulnerability of the double transition under analysis; (2) capturing the multidimensional resources that interactively build up to give rise to resilient and empowering integration and coming of age experiences. The identification of decisive multidimensional obstacles and resources present in the integration endeavour during the process of coming of age allowed us to capture differentiated routes of vulnerability, on the one hand, and resilience/ empowerment on the other. Key ingredients of both vulnerable and more resilient and empowering integration and coming of age trajectories are identified as well as their relational dynamics, enabling to address key challenges for the resilience and empowerment of young migrants in the process of negotiating their transition to adulthood amidst their integration challenges in the Luxembourgish society.